The Construction of Multisensory Models of Ancient Statuary, between Innovation and Tradition (diségno, 2024)
The research focuses on the development of a scientific methodology for the creation of copies of Cultural Heritage without scale reduction, capable of simulating the physical qualities of original materials such as marble, to allow for multi-sensory enjoyment. Using innovative technologies and traditional techniques, the process begins with a massive data survey, identifying a digital reference model. Subsequently, the construction of a ‘new original’ by 3D printing in PLA and deblocking paves the way for the creation of copies by casting with a cement mixture that can simulate the materiality of marble. The choice of materials, subjected to perceptual and thermal tests, plays a crucial role in the selection of the material to be used to replicate the characteristics of the original. The validation of the geometric results demonstrates the compatibility of the physical models with the research objective. Finally, the study introduces the concept of ‘metric reliability level’ as an essential parameter for the scientific validation of the results. The research, carried out with the collaboration of the Soprintendenza Speciale Archeologia, Belle Arti e Paesaggio of Rome and the Pontifical Commission for Sacred Archaeology, focuses on the copy of the Head of St. Elena in the Mausoleum of St. Elena in Rome, highlighting the applicability of the proposed methodology in the context of Cultural Heritage.
Keywords: 3D model; Structured Light Scanner; SfM; Head of St. Elena; 3D Printer models